AAI – the forgotten pacing mode - Domagała, Szymon; Polewczyk, Anna; Zandecki, Łukasz; Janion, Marianna (Medical Studies/Studia Medyczne, 2017)
For a long time the AAI pacing mode was commonly used in patients with sick sinus syndrome, who were treated with pacemaker. After the guideline recommendations were updated in 2013 the AAI mode was displaced by the DDDR mode, especially with atrioventricular delay management. The most important argument for this change was the risk of the development of advanced atrioventricular block in long-term observation. This situation may require changing the pacing mode to DDD and implanting a ventricular lead. However, the AAI pacing mode has many forgotten advantages and it could still be successfully used in well selected patients with sick sinus syndrome.